Salmonella Typhi Toxin Promoting - Mahmood, Walaa Shakir (American Journal of Biology and Natural Sciences, 2024)
Typhoidal Salmonellae and non-typhoidal Salmonellae (NTS) result in typhoid fever and gastroenteritis in humans. Little is understood about the function of the NTS in relation to typhoid disease progression and chronic infection, despite the known role of Salmonella typhoid toxin. We discovered that typhoid toxin and its NTS counterpart lead to distinct clinical symptoms. The PltB subunit of every toxin shows distinct glycan-binding preferences that are linked to the glycan expression profiles of host cells at the primary infection or intoxication sites targeted by each bacterium. By examining co-crystal structures of PltB subunits with distinct glycan receptor molecules, we demonstrate that they cause significant variations in glycan-binding affinities and outcomes related to virulence. Both of these subunits are chemically bonded to each other and join a homopentameric B subunit made up of PltB. It has been recently found that injecting purified typhoid toxin systemically in mice can reproduce several symptoms of typhoid fever. This discovery is very thrilling as it connects typhoid toxin to the development of typhoid fever and offers solid foundations for creating new methods for prevention and lifesaving treatments. The unique aspect of typhoid toxin is that it is only made by bacteria inside cells and, once it is created, it is released into the vacuole containing Salmonella.